2018
DOI: 10.7567/1882-0786/aaf170
|View full text |Cite
|
Sign up to set email alerts
|

Phase velocity of drifting spin wave packets in semiconductor two-dimensional electron gas

Abstract: We investigated the drift and diffusion dynamics of spin wave packets under spin–orbit effective magnetic fields in two-dimensional electron systems. A simplified model with a spin drift-diffusion equation predicted that the spin phase velocity will change over time from a large negative value to a small positive value. Kerr rotation microscopy revealed the trend we expected for the phase velocity in spin wave packets in a GaAs quantum well. Monte-Carlo simulations agreed with the experiment and showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In this study, we shed light on the dynamical response of nano-sized GaN during the excitation process owing to the potential of GaN in various electronic applications such as microwave frequency integrated circuits, lightemitting diodes, solar cells, and spin-wave devices [53][54][55]. It is reported that electrons can not move from the valence band to the conduction band until it acquires an amount of energy at least equal to the energy gap.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In this study, we shed light on the dynamical response of nano-sized GaN during the excitation process owing to the potential of GaN in various electronic applications such as microwave frequency integrated circuits, lightemitting diodes, solar cells, and spin-wave devices [53][54][55]. It is reported that electrons can not move from the valence band to the conduction band until it acquires an amount of energy at least equal to the energy gap.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%